The ethics of private equity: balancing financial returns with social responsibility - Bufalini, Andrea (2023)
This thesis explores the role of private equity in the global economy, focusing on its social impact and the relationship between financial returns and broader societal concerns. Through case studies and interviews, it addresses industry criticisms and emphasizes responsible investment practices that integrate ESG considerations. Recommendations include transparency, robust due diligence, collaboration, and impact monitoring to drive positive change and ensure long-term value creation. By embracing these recommendations, private equity can contribute to an inclusive, equitable, and sustainable future, aligning financial goals with social responsibility for both financial returns and positive societal outcomes.